Effects of polyelectrolytes on the hardness of borax decahydrate crystals - SAYAN, PERVİZ; POLAT, SEVGİ (My University, 2019)
The hardness of borax decahydrate crystals was measured using cationicpolyelectrolytes of FO4115, FO4400 and FO4990 with anionic polyelectrolytesof AN923, AN930 and AN999 as an additive. The measurements were carriedout in the indentation load range of 10 g to 30 g. It was determined that theVickers hardness (HV) decreased with increasing applied load, showing thatthe borax decahydrate crystals exhibited an indentation size effect. Vickersmicrohardness measurements revealed that pure borax decahydrate crystals hada brittle structure, yet the crystals obtained in additive media were categorizedas a soft material. The proportional specimen resistance model was applied todetermine the load-independent microhardness. The crystal hardness of boraxdecahydrate was found to change depending on the type and concentration ofpolyelectrolyte used. In addition to the mechanical properties, the thermal andphysical characteristics of borax decahydrate crystals were investigated bythermogravimetric and Fourier transform infrared spectroscopy analysis. Thecharacterization results confirmed that the polyelectrolytes were adsorbed on thecrystal’s surface.